Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. Kredit Pintar Indonesia - Andri Priadi; Aden Prawiro Sudarso (JURNAL RISET MANAJEMEN (JURMA), 2024)
This study aims to analyze the influence of employee motivation and work discipline on employee performance. Data was collected using a survey method with a questionnaire distribution technique. The respondents of this research were the staff or employees of the Collection division at PT. Smart Credit Indonesia as many as 92 respondents. The analytical method used in this study used multiple linear regression analysis with the statistical testing tool SPSS 22 (statistical program for social science) for windows. The results showed that simultaneously motivation and work discipline affect employee performance by 42.3%. Partially, motivation affects employee performance by 25.7%, while work discipline affects employee performance by 40.8% and the rest is influenced by other factors not examined in this study. Keywords: ,,